2022
DOI: 10.1002/celc.202200458
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Free‐Standing CoxP/Co3(PO4)2/C Composite Nanofiber Mats and Their Characteristics as Multi‐functional Interlayers for Lithium‐Sulfur Batteries

Abstract: The free‐standing cobalt phosphides‐based composite nanofiber mats with different compositions (CoyP/C, CoxP/Co3(PO4)2/C, where 2>x>y>1) were synthesized by electrospinning with heat treatments and applied as multi‐functional interlayers for lithium‐sulfur batteries. The polysulfide confining ability of the interlayers was evaluated by a static polysulfide adsorption test and an electrochemical conversion test using symmetric cells. The CoxP/Co3(PO4)2/C exhibited better catalytic performance for converting pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…64 On the other hand, these reducing properties of PVP could be efficiently utilized in the reduction of SnO 2 nanoparticles forming metallic Sn particles, 65 SnO x within porous carbon nanobers, 66 or reduction of threevalent Fe species into two-valent Fe, 67 preparation of graphene from graphene oxide, 59 and reducing phosphates to phosphides. 68 PVP is soluble in many solvents, but EthOH and distilled water are the most commonly used alone or in combination as they are comparably green. However, DMF and isopropanol (i-PrOH) are sometimes also used.…”
Section: Solution Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…64 On the other hand, these reducing properties of PVP could be efficiently utilized in the reduction of SnO 2 nanoparticles forming metallic Sn particles, 65 SnO x within porous carbon nanobers, 66 or reduction of threevalent Fe species into two-valent Fe, 67 preparation of graphene from graphene oxide, 59 and reducing phosphates to phosphides. 68 PVP is soluble in many solvents, but EthOH and distilled water are the most commonly used alone or in combination as they are comparably green. However, DMF and isopropanol (i-PrOH) are sometimes also used.…”
Section: Solution Preparationmentioning
confidence: 99%
“…88 However, when synthesizing more complex oxygen-rich compounds, utilizing oxygen-free precursors (with weak oxidizing properties), or aiming for lower carbon contents, a pre-oxidation step is required. 44,61,68 According to Kim et al, atomic reorganization of PVP starts at 210 °C, combustion of PVP occurs in the O 2 atmosphere at 290 °C and thermal decomposition of the polymer starts at 350 °C. 73 Hieu et al and Szilágyi et al concluded that complete thermal decomposition of PVP approximately occurs at 450 °C.…”
Section: Heat Treatmentmentioning
confidence: 99%
See 3 more Smart Citations